2014
DOI: 10.1038/srep04134
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the antimicrobial mechanism of TiO2-based nanocomposite films in a pathogenic bacterium

Abstract: Titania (TiO2)-based nanocomposites subjected to light excitation are remarkably effective in eliciting microbial death. However, the mechanism by which these materials induce microbial death and the effects that they have on microbes are poorly understood. Here, we assess the low dose radical-mediated TiO2 photocatalytic action of such nanocomposites and evaluate the genome/proteome-wide expression profiles of Pseudomonas aeruginosa PAO1 cells after two minutes of intervention. The results indicate that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
254
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 369 publications
(261 citation statements)
references
References 59 publications
(103 reference statements)
5
254
1
1
Order By: Relevance
“…The total of 31 chemicals was quantified in cell cultures grown on either acetate or pyruvate (Supplementary Table S8). Metabolites were extracted as previously described (Kubacka et al, 2014) and analyzed on three complementary platforms including mass spectrometry (MS) with gas and liquid chromatography (LC) and capillary electrophoresis (CE) separations (gas chromatography-quadrupole time-of-flight (QTOF)-MS, LC-QTOF-MS and CE-TOF-MS). As indicated in Supplementary Table S8, these analytical platforms matched the nature of the chemical species.…”
Section: Genome Annotationmentioning
confidence: 99%
“…The total of 31 chemicals was quantified in cell cultures grown on either acetate or pyruvate (Supplementary Table S8). Metabolites were extracted as previously described (Kubacka et al, 2014) and analyzed on three complementary platforms including mass spectrometry (MS) with gas and liquid chromatography (LC) and capillary electrophoresis (CE) separations (gas chromatography-quadrupole time-of-flight (QTOF)-MS, LC-QTOF-MS and CE-TOF-MS). As indicated in Supplementary Table S8, these analytical platforms matched the nature of the chemical species.…”
Section: Genome Annotationmentioning
confidence: 99%
“…The mechanism of FeOx charge photo-generation will not be described in this study since it has been recently reported in our laboratory [16]. Also the TiO 2 -PE mediated bacterial inactivation has been reported widely in the open literature [1][2][3]18]. Below Eqs.…”
Section: Results An Discussionmentioning
confidence: 99%
“…The intervention of FeOx injecting e − into TiO 2 is suggested in Eqs. (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13):…”
Section: Suggested Mechanism Of Bacterial Inactivation Bymentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 has received great attention since the last two decades owing to its high refractive index, large dielectric constant, immense physio-chemical stability, colossal inertness in austere ambiences, reduced toxicity, low cost and hassle free developmental methods. Presently, TiO 2 is actively employed in optoelectronic sensors [1], waveguides [2], photovoltaic cells [3], photo catalysts [4], as pigments in paints [5] and food (for colouring and additives), biomaterials (as bone substituents and cardiovascular implants) [6] and neutralizing agent against microbial organisms [7]. TiO 2 , being a remarkable photocatalyst in UV region, lacks photophysical properties in visible region due to its large bandgap (3.25 eV).…”
Section: Introductionmentioning
confidence: 99%